2015
DOI: 10.2105/ajph.2014.302378
|View full text |Cite
|
Sign up to set email alerts
|

State Barriers to Appropriating Public Health Emergency Response Funds During the 2009 H1N1 Response

Abstract: Purchasing barriers were associated with delayed use of PHER funds. Moreover, the cumulative effect of any 3 barriers hampered the allocation of funds. Understanding barriers to using funds can inform future funding guidance for improved efficiency of response efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Of the 13 infrastructural studies, 6 examined organizational or structural components, such as immunization advisory committees and the laws governing immunization information systems, and their operation or effects. 24 29 Three studies examined the mechanisms of change within the health system, such as accreditation and incentives, 30 32 and 3 studies focused on system outcomes and outputs. 33 35 Of the 13 infrastructural articles, 1 reported on the development of a monitoring and assessment tool for implementation of the International Health Regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 infrastructural studies, 6 examined organizational or structural components, such as immunization advisory committees and the laws governing immunization information systems, and their operation or effects. 24 29 Three studies examined the mechanisms of change within the health system, such as accreditation and incentives, 30 32 and 3 studies focused on system outcomes and outputs. 33 35 Of the 13 infrastructural articles, 1 reported on the development of a monitoring and assessment tool for implementation of the International Health Regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Across the work of WHO, the law of an individual Member State may act as an intervention tool, 18 as an important influence on the health of the population 19 or as a barrier to action 20 , 21 . While the existence of specific laws is not sufficient in itself for a strong health system generally or for effective legal interventions in specific threats, it is clear that the law matters for effective health practice.…”
Section: National Legal Infrastructurementioning
confidence: 99%
“…Even when funds are made available, allocation of those funds may prove difficult. Yeager, Hurst, and Menachemi (2015), in a study of allocation of PHER funding during H1N1, found that purchasing barriers and other administrative barriers such as fund transfer issues hindered the allocation of H1N1 funds.…”
Section: Literature Reviewmentioning
confidence: 99%